The Influence of Kiai Leadership, Pesantren Culture, and Information Technology on Santri Loyalty - Nur, Muhamad Amin; Antariksa, Walid Fajar; Wahidmurni; Wahyudin, Aji (Al-Hayat: Journal of Islamic Education, 2024)
The loyalty of students in Pesantren (Islamic Boarding School) is influenced by the leadership of the Kiai, religious culture, and information technology. The purpose of this study is to understand the influence of the leadership style of the Kiai and the culture of the Islamic boarding school on the loyalty of students with information technology as a moderator variable. This study combines quantitative and qualitative approaches with a mixed method and a multi-case study. Data were collected through questionnaires, semi-structured interviews, and documentation. Quantitative analysis used moderate regression analysis (MRA), while qualitative analysis was conducted using thematic analysis. Data triangulation and member checks ensured the validity of the results. The study results indicate that kiai leadership and pesantren culture significantly influence students' loyalty at the Nurul Jadid Probolinggo and Al-Hikam Malang pesantren. With a personal approach, Kiai's inspiring and humanistic leadership builds a strong emotional bond with students. In addition, the pesantren culture that emphasises religious values ​​and character forms student loyalty. Information technology also supports communication, operational efficiency, and more enjoyable learning. Regression analysis shows that pesantren culture has a more significant influence than leadership style, with an R² of 0.670 indicating a moderate relationship between the independent and dependent variables. The implications of this study indicate that Kiai's leadership and the pesantren's culture play an important role in building the loyalty of the students, which is strengthened by the application of information technology. The limitations of this study lie in the scope, which is limited to two pesantren, so the results cannot be generalised to other pesantren.